Droplet digital PCR for identifying copy number variations in patients with primary immunodeficiency disorders. (21st December 2021) - Woon, See-Tarn; Mayes, Julia; Quach, Alexander; Longhurst, Hilary; Ferrante, Antonio; Ameratunga, Rohan
Abstract: Primary immunodeficiency disorders comprise a rare group of mostly monogenic disorders caused by inborn errors of immunity. The majority can be identified by either Sanger sequencing or next generation sequencing. Some disorders result from large insertions or deletions leading to copy number variations (CNVs). Sanger sequencing may not identify these mutations. Here we present droplet digital PCR as an alternative cost-effective diagnostic method to identify CNV in these genes. The data from patients with large deletions of NFKB1, SERPING1, and SH2D1A are presented. Abstract : Digital droplet PCR is new method which can be used to determine copy number variations in primary immunodeficiency diseases. Graphical Abstract: